2017
DOI: 10.1186/s11671-017-2297-0
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Driven Photocatalytic Performance of N-Doped ZnO/g-C3N4 Nanocomposites

Abstract: N-doped ZnO/g-C3N4 composites have been successfully prepared via a facile and cost-effective sol-gel method. The nanocomposites were systematically characterized by XRD, FE-SEM, HRTEM, FT-IR, XPS, and UV-vis DRS. The results indicated that compared with the pure N-doped ZnO, the absorption edge of binary N-doped ZnO/g-C3N4 shifted to a lower energy with increasing the visible-light absorption and improving the charge separation efficiency, which would enhance its photocatalytic activity. Compared with the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…ZnO catalyst has potential to achieve improved photocatalytic performance as it absorbs over an appreciable region of the UV-Vis spectrum (Hamid, The, & Lai, 2017). But it is more susceptible to photo corrosion as compared to TiO 2 , shows less charge separation efficiency and it has poor light absorbance for solar irradiation (Kong, Zhai, Wang, Zhao, & Li, 2017).…”
Section: Short Communicationmentioning
confidence: 99%
“…ZnO catalyst has potential to achieve improved photocatalytic performance as it absorbs over an appreciable region of the UV-Vis spectrum (Hamid, The, & Lai, 2017). But it is more susceptible to photo corrosion as compared to TiO 2 , shows less charge separation efficiency and it has poor light absorbance for solar irradiation (Kong, Zhai, Wang, Zhao, & Li, 2017).…”
Section: Short Communicationmentioning
confidence: 99%
“…The results revealed that the addition of IPA showed a significant decrease in the degradation of MB dye by quenching hydroxyl radical ( • OH) produced in the reaction mixture, implying the dominant role of • OH radicals in the process of MB dye degradation. Furthermore, with the addition of BQ and AO, the photodegradation of MB is slightly reduced, providing further evidence of the presence of hydroxyl radicals as the main reactive species [63,64]. The BQ captures photogenerated electrons and reduces the possibility of double-electron reduction, while AO captures the hole during the photocatalytic reaction process.…”
Section: The Mechanism Behind the Photocatalytic-degradation Of Mbmentioning
confidence: 81%
“…11 ) for methylene blue (MB) degradation [ 92 ]. Synthesizing and preparing of the candidate by doping metals such as Cu and Fe [ 93 95 , 96 ] and non-metals such as B, C, O, or S [ 97 100 ], and co-doping [ 101 103 ] has been widely used by many scientists for water and environmental treatment. A promising solution to environmental depollution [ 104 – 106 ] is the combination of noble metals and g-C 3 N 4 [ 107 112 ].…”
Section: Reviewmentioning
confidence: 99%